Simulasi Numerik pada Rectangular Cylinder dekat Dinding yang mengunakan Diffuser dan tanpa Diffuser dengan Mengunakan K Model - Nuzul Hidayat - (Jurnal Ilmiah Poli Rekayasa, 2016)
Rectangular Cylinder with a rectangular cross section is also used as a building, the architectural features of the building, the internal flow geometry, and beam. In addition, flow around Rectangular Cylinder can produce local instability and can lead to global instability. Diffuser can work for both conditions by reducing the drag force and increase down force. Diffuser is designed to change the fluid kinetic energy into potential energy in the form of pressure. The increase in pressure that occurs in the diffuser will generate a positive pressure gradient or also called adverse pressure gradient (APG). In this case Rectangular Cylinder that use Diffuser And Without Diffuser at Re 1 x 106 obtained graphs of: (a) Drag Coefficient (Cd) (b) Lift Coefficient (Cl) and (c) Velocity contour in the area of mid span numerically using the software Fluent 6.3.26 with k ε- turbulence models that Standard are two-dimensional (2D). On the Cylinder Rectangular diffuser values obtained using 1:36 Cd and Cl -0.81 and Rectangular Cylinder without diffuser obtained value Cd Cl 0:47 and 1:53, clearly visible on the use Rectangular Cylinder diffuser turns diffuser provides greater Cd and Cl negative or increase down force. The treatment is to eliminate the other side upper corner on the front of a quarter circle with r = 0.1, this produces a different contour velocity when compared experiment this treatment capable of eliminating reattached flow on the upper side area.